Bibliometric Analysis: Research on Resilience in Indonesia 2014 - 2024 - Amien Wahyudi; Mungin Eddy Wibowo; Mulawarman; Mohammad Japar; Shopyan Jepri Kurniawan (Universitas Negeri Semarang, 2024)
This study aims to examine bibliometric research on resilience in Indonesia from 2014 to 2024. Emerging themes offer critical discussions for theory development and future research. To achieve this goal, 900 writings on resilience in Indonesia were analyzed using bibliometrics. The data for this study was obtained from the Google Scholar database. The research findings show that research on resilience has increased since 2018. This study also shows that resilience research related to the stressors of children with special needs still needs to be done. Penelitian ini bertujuan untuk mengkaji penelitian bibliometrik tentang ketahanan di Indonesia dari tahun 2014 hingga 2024. Tema-tema yang muncul menawarkan diskusi kritis untuk pengembangan teori dan penelitian di masa depan. Untuk mencapai tujuan tersebut, 900 tulisan tentang ketahanan di Indonesia dianalisis menggunakan bibliometrik. Data untuk penelitian ini diperoleh dari database Google Scholar. Temuan penelitian menunjukkan bahwa penelitian mengenai resiliensi mengalami peningkatan sejak tahun 2018. Penelitian ini juga menunjukkan bahwa penelitian resiliensi terkait stresor pada anak berkebutuhan khusus masih perlu dilakukan.